Pemberdayaan masyarakat melalui program CSR PT. Angkasa Pura I Yogyakarta (studi kasus UMKM Madu Hutan Raya dan Mina Kembar) - Bayu Mahendra (Jurnal Agercolere, 2019)
This study aimed to (1) assessing the empowerment process through Corporate Social Responsibility (CSR) programs carried out by PT. Angkasa Pura I on Micro Small Medium Enterprises (2) assessing the development of MSMEs that utilize CSR programs. This research is a qualitative research with a method of carrying out case studies, taking informants purposively. Data collection techniques used are in-depth interviews, observation, and documentation while for the data analysis techniques using descriptive qualitative and the validity of the data obtained tested by triangulation of data collection techniques. The results of this study conclude that, (1) the process of empowerment through a CSR program implemented by PT. Angkasa Pura I on MSMEs, started from the capacity building phase and did not go through the awareness stage and (2) development of MSMEs utilizing CSR programs of PT. Angkasa Pura I had been running well which was marked by the beginning of the development of business assets and also business mindset.